ANALISIS USAHATANI TOMAT (Lycopersicon esculentum Mill) DI DESA MANDESAN KECAMATAN SELOPURO KABUPATEN BLITAR - Efendi, Yusuf (Universitas Islam Balitar, 2016)
This research was conducted in Farmers Group Karya Maju located in the village Mandesan Selopuro Blitar districts, the data retrieved from the main data of the farmer members of the group as respondents, the research method used is observation, interview and Analisia. The results showed that 1) Analysis of farming tomatoes in Farmers Karya Maju allocate available resources effectively and efficiently to earn income at a certain time of Rp. 44,804,822, - 2) A financial analysis of farming tomatoes in Karya Maju Farmers Group to determine whether farming is done feasible and profitable to be developed or is said to be still in efensiensi level. R / C ratio of 1.8 indicates that the worth of the cost of Rp. 54,095,828, - will be obtained receipts by 1.8 times as much. In other words, the sale of tomatoes reached 1.8% of the capital that has been allocated. R / C Ratio worth more than 1, indicating that the tomato farming qualified / eligible to be developed.